Tubercular scleritis - Sharma, R; Marasini, S; Nepal, B P (Kathmandu University Medical Journal, 2012)
Scleritis is a severe painful inflammatory process centred in the sclera. A scleritis may be a harbinger of many systemic diseases so that it is important to exclude multisystem disease. We describe a case of unilateral tubercular anterior nodular non-necrotizing scleritis. Anterior nodular non-necrotizing scleritis is relatively an uncommon manifestation of tuberculosis. It may be difficult to diagnose and manage the disease. However, good history, detail clinical evaluation, appropriate and timely management shows a good response to the disease. DOI: http://dx.doi.org/10.3126/kumj.v8i3.6228 Kathmandu Univ Med J 2010;8(3):352-6